Energy and exergy analyses of porous baffles inserted solar air heaters for building applications - Bayrak, Fatih; Öztop, Hakan Fehmi; Hepbasli, Arif (Elsevier Science Sa, 2013)
This study deals with performance assessment of porous baffles inserted solar air heaters (SAHs) using energy and exergy analysis methods. The porous baffles (PBs) with different thicknesses are used as passive element inside heaters. Closed-cell aluminum foams are chosen as porous materials with thicknesses of 6 mm and 10 mm and a total surface area of 50 cm(2). They are placed sequentially and staggered manner onto the SAH. The measured parameters are the inlet and outlet temperatures, the absorbing plate temperatures, the ambient temperature and the solar radiation. These measurements are performed at two various air mass flow rates of 0.016 kg/s and 0.025 kg/s. Using the first and second laws of thermodynamics, energy and exergy efficiencies of the SAHs are calculated and presented for different parameters. In the experiments, five types of solar air heaters are tested and compared with each other in terms of their efficiencies. The obtained results showed that the highest collector efficiency and air temperature rise are achieved by SAHs with a thickness of 6 mm and an air mass flow rate of 0.025 kg/s whereas the lowest values are obtained for the SAH with non-baffle collectors and an air mass flow rate of 0.016 kg/s. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Building; Solar air heater; Solar collector; Porous material; Exergy; Sustainability